2011
DOI: 10.1044/1092-4388(2010/10-0010)
|View full text |Cite
|
Sign up to set email alerts
|

Psycholinguistic Profiling Differentiates Specific Language Impairment From Typical Development and From Attention-Deficit/Hyperactivity Disorder

Abstract: Purpose Practitioners must have confidence in the capacity of their language measures to discriminate developmental language disorders from typical development and from other common disorders. In this study, psycholinguistic profiles were collected from 3 groups: children with specific language impairment (SLI), children with attention-deficit/hyperactivity disorder (ADHD), and children with typical development (TD). The capacity of different language indices to successfully discriminate SLI cases from TD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
104
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 48 publications
4
104
2
2
Order By: Relevance
“…The SRep tasks target linguistic knowledge and draw on grammaticality, plausibility, prosody and lexicality (Polišenská, Chiat, & Roy, 2015). SRep has been proven to be a good clinical marker for the identification of children with language impairment in monolingual populations (Archibald & Joanisse, 2009;Conti-Ramsden, Botting, & Faragher, 2001;Laws & Bishop, 2003;Redmond, Thompson, & Goldstein, 2011). This is due to the test's high sensitivity and specificity.…”
Section: Sentence Repetition Taskmentioning
confidence: 99%
“…The SRep tasks target linguistic knowledge and draw on grammaticality, plausibility, prosody and lexicality (Polišenská, Chiat, & Roy, 2015). SRep has been proven to be a good clinical marker for the identification of children with language impairment in monolingual populations (Archibald & Joanisse, 2009;Conti-Ramsden, Botting, & Faragher, 2001;Laws & Bishop, 2003;Redmond, Thompson, & Goldstein, 2011). This is due to the test's high sensitivity and specificity.…”
Section: Sentence Repetition Taskmentioning
confidence: 99%
“…Although these two common disorders frequently co-occur, studies exploring language abilities of children with ADHD or directly comparing these two high-incidence populations are relatively few (McInnes, Humphries, Hogg-Johnson, & Tannock, 2003;Redmond et al, 2011). Furthermore, in clinical contexts language related problems are seldom screened for as part of the assessment procedure for AD/HD.…”
mentioning
confidence: 99%
“…The consequence is often behaviour with a negative effect on social and academic interaction. For some children also their language development may be compromised (Redmond, Thompson, & Goldstein, 2011). AD/HD is the most frequent psychiatric diagnosis given to children with language impairments (Miniscalco et al, 2006;Snowling, Bishop, Stothard, Chipchase and Kaplan, 2006;Tirosh & Cohen, 1998).…”
mentioning
confidence: 99%
“…Several studies have found that SLI children perform poorly between their typically developing (TD) peers, and other clinical groups (e.g. Redmond, 2005;Stokes et al, 2006;Archibald et al, 2009;Seeff-Gabriel et al, 2010;Riches et al, 2010;Redmond et al, 2011;Thordardottir et al, 2012). Stokes et al (2006) also found that SR has high specificity and sensitivity for identification of Cantonese SLI children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies (e.g. Alloway & Gatthercole, 2005;Redmond, 2005;Riches, Loucas, Baird, Charman, & Simonoff, 2010;Redmond, Thompson, & Goldstein, 2011) have shown that the errors made by children with SLI differ from those made by children with autism, ADHD or dyslexia both qualitatively (error types) and quantitatively (frequency of errors).…”
Section: Literature Reviewmentioning
confidence: 99%